2001
DOI: 10.1016/s0736-0266(01)00048-1
|View full text |Cite
|
Sign up to set email alerts
|

The angiogenic response to skeletal injury is preserved in the elderly

Abstract: Angiogenesis is essential for normal bone formation and repair. Avascularity characterizes aberrant fracture union in the elderly, while angiogenic mechanisms during cutaneous wound repair are attenuated in aged humans. We hypothesized that skeletal injury results in local (circulating) and systemic (fracture site) 'angiogenic' responses and that these reparative mechanisms are attenuated with advanced patient age. This prospective study examined peripheral blood and fracture hematoma from 31 patients, 16 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 36 publications
0
39
0
6
Order By: Relevance
“…Lu et al reported agerelated changes in fracture healing in rats [35]. Street et al found that angiogenesis at the fracture site and the response of growth factor to fracture in the elderly human was preserved [36]. Moreover, age was considered as factor for non-union after internal fixation of femoral neck fractures and clavicular non-union [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al reported agerelated changes in fracture healing in rats [35]. Street et al found that angiogenesis at the fracture site and the response of growth factor to fracture in the elderly human was preserved [36]. Moreover, age was considered as factor for non-union after internal fixation of femoral neck fractures and clavicular non-union [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with other reports showing a high concentration of VEGF during the inflammatory phase of fracture healing in humans. 26,27 Street et al 26 demonstrated highly elevated VEGF concentrations in fracture hematoma and peripheral blood of 32 patients immediately after trauma. Grad et al 27 also observed highly elevated VEGF concentrations in 55 polytraumatized patients within the first week after trauma, with the highest level in the second week.…”
Section: Vegf In Fracture Healingmentioning
confidence: 99%
“…3,4,9 The angiogenic response to fracture is also preserved in fracture repair in older individuals. 3,4,32 In contrast, in diabetic animals, there is impaired stimulation of PDGF associated with their delayed fracture repair. 33 These two processes, age and diabetes, then, appear to slow fracture repair through separate mechanisms.…”
Section: Up-regulated Genes In Callus Of Old Ratsmentioning
confidence: 99%